The The Influence of Self-Esteem and Emotional Intelligence on Aggressiveness Among Students of SMKN X In Padang - Nadia Salsabila Luthfa; Nurisma Sari; Syarifah History Noversya; Yenni Kurniawati (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
This study aims to analyze the relationship between self-esteem, emotional intelligence, and aggression among students at SMKN X in Padang. This study uses a quantitative approach with a correlational design, where the research population consists of 1,109 students spread across seven majors and three grade levels (X, XI, XII). The sample consisted of 164 students from grades XI and XII, selected using cluster sampling technique. Data were collected using three standardized instruments, namely the aggression scale from Buss & Perry (1992), the self-esteem scale adapted by Sari (2009) from Felker, and the emotional intelligence scale based on the theory of Salovey and Goleman (2015). The results of multiple regression analysis showed that self-esteem and emotional intelligence had a significant effect on student aggression, with self-esteem being the more dominant factor. Together, these two variables can explain 86.1% of the variation in student aggression. These findings indicate that increasing healthy self- esteem and emotional intelligence can reduce aggressive behavior among students